Hellenistic Alexandria: Celebrating 24 Centuries – Papers Presented at the Conference Held on December 13–15 2017 at Acropolis Museum, Athens - Christos S. Zerefos; Marianna V. Vardinoyannis (Archaeopress Archaeology, 2018)
Hellenistic Alexandria: Celebrating 24 Centuries presents the proceedings of a conference held at the Acropolis Museum in Athens, on December 13–15, 2017, and includes high-level dialogues and philosophical discussions between international experts on Hellenistic Alexandria. The goal was to celebrate the 24 centuries which have elapsed since its foundation and the beginning of the Library and the Museum of Alexandria. The conference was divided into two parts, to include in the first part archaeology, history, philosophy, literature, art, culture and legal issues and in the second part science, medicine, technology and environment. A total of 28 original and peer-reviewed articles point to the importance of the brilliantly-original ideas that emerged during the Hellenistic age and the curious modernity of the whole atmosphere of the time. The range of presented topics covers a variety of new data on the foundation of Alexandria to comparison between Ptolemaic Alexandria and Ptolemaic Greece through philosophy, culture and drama to the forgotten revolution of science, medicine and the prevailing climatological and geophysical conditions throughout the Hellenistic Period. The conference and its proceedings were co-sponsored by the Μarianna V. Vardinoyannis Foundation, the Acropolis Museum, the Alexandria Center for Hellenistic Studies at Bibliotheca Alexandrina and the Mariolopoulos-Kanaginis Foundation for the Environmental Sciences. The Publication also celebrates the 10th anniversary of the Alexandria Center for Hellenistic Studies, a joint collaboration between the Bibliotheca Alexandrina, the Vardinoyannis Foundation and the University of Alexandria. Scholars from around the world follow the Center's programme in various specialisations, ranging from historyliterature- art, to archaeology and architecture-philosophy, and science.